In vitro germination of passion fruit seeds in the function of tegument removal and culture media - Faria, Glaucia A. [UNESP]; Lopes, Beatriz G.; Suares-Rocha, Paula [UNESP]; Ferreira, Antonio F. A.; Maltoni, Katia L. [UNESP]; Silvério Junior, Luiz H.; Pigari, Lucas B. [UNESP]; Felizardo, Lucas M. [UNESP]; Furlani Júnior, Enes [UNESP] (FapUNIFESP (SciELO), 2023)
The presence of salts in the culture medium and the addition of phytohormones, necessary to break seed dormancy in the in vitro germination of passion fruit, can induce critical values of osmotic potential. This can change the membrane permeability of seeds, affecting the hydration rate, enzyme release, ion transport, pH, and inhibitor values, which may decrease germination percentage. The aim of this study was to evaluate different types of culture media, composed of other substances, combined with mechanical techniques of tegument removal to determine the most appropriate culture medium for the in vitro germination of Passiflora edulis (Sims flavicarpa Deg.) seeds obtained by open pollination. The experimental design was completely randomized in a 10 × 3 factorial scheme (10 culture media × three types of seed-intact, scarified, and cut), with eight replicates and five seeds per plot. Scarified seeds cultivated in a medium composed of a commercial substrate and gibberellic acid presented a higher percentage of germination than intact or cut seeds cultivated in different concentrations of Murashige & Skoog (MS) medium. Scarification is a satisfactory method for breaking the dormancy of passion fruit seeds, and commercial substrates Bioflora® enriched with gibberellic acid may replace in vitro germination.
Germinação in vitro de sementes de maracujá em função da remoção do tegumento e meios de cultura
Keywords: abiotic stress; non-parametric tests; Passiflora edulis (Sims flavicarpa Deg.); seeds viability; tissue culture